Perancangan Kawasan Masjid At-Taqwa Desa Aursati Kampar Dengan Pendekatan Arsitektur Islam - Muhd Arief Al Husaini; Wahyu Hidayat; R. Lisa Suryani; Muhammad Rijal; Mashuri Mashuri (Journal of Community Engagement Research for Sustainability, 2021)
The mosque is an important element for Muslims both in performing worship and muamalah activities so that it is undeniably a religious center. The mosque experienced the dynamics of significant development ranging from general geometric shapes to modern architectural styles. At-Taqwa Mosque has not been maximized as a house of worship because muhrim privacy is not well achieved, does not accommodate worshippers at large events, lacks other facilities. The management cooperates in the service activities to realize the documents of the design of the Taqwa Aursati mosque area. This activity is descriptive qualitative by collecting data through observation and interview. An activity approach is a bottom-up approach that is with the smoothing of the user's interests and desires. The result of this activity is to obtain documents designing the At-Taqwa mosque area by applying the concept of Islamic architecture. The design provides facilities based on zoning i.e. transition zones, mosque zones, and educational zones. This document is useful for the committee for the development of the At-Taqwa mosque as a guide in the implementation of the construction of the mosque.